Developing Standardised Accounting Information System (AIS) Course for Iraqi Higher Education: A Conceptual Framework - Lallo, Naseem Yousif; Selamat, Mohamd Hisyam (Asian Journal of Business and Accounting, 2013)
One of the challenges in global educational reform is a need to come out with a curriculum that is capable of delivering 21st century knowledge to the students in all areas of studies of Higher Education Institutions (HEIs). This is to ensure that competent graduates are produced from HEIs. Undoubtedly, the Iraq post-wars and economic sanctions have led to poor states of technology and education in the country. As part of the Iraqi accounting education, accounting information system (AIS) course content has been affected by the Iraqi circumstances, since the global trend demands a technologydriven course. This results in Iraq lagging behind compared to other countries, even amongst developing countries. Thus, there is a need to determine the factors that need to be considered while developing an AIS course in Iraq in order to make it at on par with international standards. To assist in this process this paper proposes a conceptual framework which highlights AIS course content that need to be considered in Iraq. Keywords: AIS, Course, HEIs, technology-driven, conceptual framework.